2015
DOI: 10.2152/jmi.62.177
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary soy protein on skeletal muscle volume and strength in humans with various physical activities

Abstract: The supplementation of soy protein would be one of the effective foods which prevent the skeletal muscle atrophy caused by immobilization or unloading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 18 publications
1
20
0
1
Order By: Relevance
“…weight maintenance or diet-induced modest weight loss), on muscle composition in older adults with overweight or obesity. Protein supplementation (10 g/day) was associated with increased thigh muscle cross-sectional area (MSCA) in bedridden, frail older adults (>70 years), whereas the current study population represents the average US older adult who is still active, independent, and not severely protein-malnourished [ 53 ]. Therefore, current results suggest that higher dietary protein intake for 12 weeks does not influence muscle composition in healthy older adults with overweight or obesity.…”
Section: Discussionmentioning
confidence: 99%
“…weight maintenance or diet-induced modest weight loss), on muscle composition in older adults with overweight or obesity. Protein supplementation (10 g/day) was associated with increased thigh muscle cross-sectional area (MSCA) in bedridden, frail older adults (>70 years), whereas the current study population represents the average US older adult who is still active, independent, and not severely protein-malnourished [ 53 ]. Therefore, current results suggest that higher dietary protein intake for 12 weeks does not influence muscle composition in healthy older adults with overweight or obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Effect of protein source on muscle hypertrophy may vary depending on exercise intensity as well. For example, Hashimoto et al had reported the soy protein supplementation increased skeletal muscle volume compared with caseinate supplementation in the subjects under the low physical activity but not high physical activity [24]. Additionally, in the bedridden patients, caseinate supplementation significantly increased skeletal muscle volume than no supplementation while its significant increase was not observed by soy protein supplementation [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, this study did not demonstrate any differences in exercise capacity between the different supplementation groups. Conversely, genistein or soy supplementation has been shown to provide several benefits in vivo or in vitro on muscle, including preventing atrophy [ 19 , 20 ], modulating metabolism [ 21 , 22 ], and promoting regeneration [ 23 , 24 ]. Here, we show that SPE, SPC and SPI consumption led to increased muscle function compared with MPI, did not display any detrimental effects and were equivalent in efficacy to WPI.…”
Section: Discussionmentioning
confidence: 99%